Challenges and trends in green finance and environmental policy in East African countries: A bibliometric and policy analysis - Samatar, Elmi Hassan (Edelweiss Applied Science and Technology, 2025)
This study examines the challenges and trends in green finance and environmental policy in East African countries (EAC), focusing on how green finance contributes to carbon emission reduction, renewable energy adoption, and sustainable land use. Using a bibliometric and policy analysis approach, the study draws on 147 peer-reviewed articles published between 2017 and 2024 and indexed in the Scopus database. VOSviewer was applied to map authorship patterns, co-citation networks, keyword occurrences, publication trends by year, and the geographical distribution of research influence. The findings reveal limited regional research output, with only 523 authors contributing to the domain, highlighting a substantial research gap compared to global trends. Three core thematic clusters emerged from the analysis: green financial instruments (e.g., bonds and fintech), policy and sustainability frameworks, and methodological innovations in econometrics. Interest peaked in 2022 but has since declined, indicating saturation in broader themes and a need for localized studies. There are disparities in regional publications, particularly with influential countries like China, the USA, and the UK. Contributions from African nations, especially the EAC, reveal institutional and capacity gaps. Challenges include a lack of standardized definitions for green financing, poor policy integration, and limited collaboration. This paper recommends enhanced regional research on green finance, policy alignment, institutional strengthening, and international cooperation to optimize green finance for sustainable development in the EAC. Future research should focus on context-driven financial models, regional public-private partnerships, and targeted capacity-building efforts to address gaps and enhance environmental sustainability in the region.